Increased blood transfusion and its impact in patients having tracheostomy while on extracorporeal membrane oxygenation. (March 2019) - Harris, Dwight D.; Shafii, Alexis E.; Baz, Maher; Tribble, Thomas A.; Ferraris, Victor A.
Introduction: Tracheostomy has been utilized in combination with venovenous extracorporeal membrane oxygenation (VV-ECMO) to enable early spontaneous breathing and minimize sedation requirements. Tracheostomy has been previously reported to be safe in patients supported on VV-ECMO; however, the impact of tracheostomy on blood loss in VV-ECMO patients is unknown. Methods: We analyzed VV-ECMO patients with and without tracheostomy over a 5-year period. In order to avoid other potential sources of blood loss not related to tracheostomy or ECMO-related blood loss, patients who underwent a recent surgery prior to ECMO or during ECMO (other than tracheostomy) were excluded. Results: Sixty-three patients meeting the inclusion criteria were identified (tracheostomy n=30, non-tracheostomy n=33). Tracheostomy patients were found to require more daily transfusions of red blood cells (RBC) (0.47 [0.20-1.0] vs. 0.23 [0.06-0.40] units/day, p=0.02) and total blood products (0.60 [0.32-1.0] vs. 0.31 [0.10-0.50] units/day, p=0.01). Conclusions: These results suggest that tracheostomy while on VV-ECMO predisposes patients to increased transfusion burden. Based on previous research, this increased transfusion burden could potentially be linked to increased complications and mortality.